2015
DOI: 10.1177/1524839915588293
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Health of Formerly Imprisoned Persons in a Distressed Neighborhood Through a Community Collaborative Board

Abstract: This article provides a case study evaluating the structure and dynamic process of a Community Collaborative Board that had the goal of creating an evidence-based substance abuse/health intervention for previously incarcerated individuals. Meeting agendas, attendance, minutes, video recording of meetings, and in-depth interviews with 13 Community Collaborative Board members were used to conduct an independent process evaluation. Open coding identified quotes exemplifying specific themes and/or patterns across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Census Bureau 2015; U.S. Department of Justice 2014), the impact of a criminal record on employment is confounded with race (Alexander 2010; Pager 2003; Smith and Jemal 2015). Income and education factors, which are integrally related and occur along racial and ethnic lines, are significant predictors of health status (Sambamoorthi and McAlpine 2003; Viruell-Fuentes et al 2012).…”
mentioning
confidence: 99%
“…Census Bureau 2015; U.S. Department of Justice 2014), the impact of a criminal record on employment is confounded with race (Alexander 2010; Pager 2003; Smith and Jemal 2015). Income and education factors, which are integrally related and occur along racial and ethnic lines, are significant predictors of health status (Sambamoorthi and McAlpine 2003; Viruell-Fuentes et al 2012).…”
mentioning
confidence: 99%
“…Social workers with CTC could: 1) address oppressive sociopolitical contexts; 2) create therapeutic alliances that validate the client’s reality and experiences; 3) help clients navigate oppressive systems of care, while simultaneously acting to change those systems; 4) recognize and challenge personal biases and the biases of others; and 5) take collaborative action with communities to address socio-structural determinants of health inequities (Hernandez et al, 2005; Garcia et al, 2009; Mullaly, 2002; Sakamoto & Pitner, 2005). This process includes holding themselves accountable for reflecting on power dynamics; continuously examining how personal biases, assumptions and normative values influence perceptions of differences between individuals; owning one’s contributions to social injustice; and developing partnerships that forge a war on oppression and privilege rather than against individuals trapped in marginalized statuses (Smith & Jemal, 2015; Garcia et al, 2009; Sakamoto & Pitner, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…A manuscript reporting the findings is currently being reviewed for publication. Results showed that board members felt comfortable expressing their opinions in the meetings, and there was a high level of satisfaction with the project (Smith & Jemal, revise and resubmit). …”
Section: Methodsmentioning
confidence: 99%